A numerical investigation of VMS-POD model for darcy-brinkman equations - G. Eroglu, Fatma; Kaya, Songul; Rebholz, Leo (Proceedings of the World Congress on Engineering, 2018)
We extend the variational multiscale proper orthogonal decomposition reduced order modeling (VMSPOD) to flows governed by double diffusive convection. We present stability and convergence analysis for it, and give results of numerical tests on a benchmark problem to show the efficiency of the approach.
Keywords: Variational multiscale; Proper orthogonal decomposition; Double-diffusive; Reduced order models